How Undergraduate EFL Writers Construct Thesis Discussion Sections : A Comparative Genre Study at Two Universities - Mustaqim, Muhammad Haris; Sylvia, Rizka; Siraj, Siraj; Najmuddin, Najmuddin (Indonesian Research Journal on Education, 2025)
This study investigates how undergraduate EFL writers construct thesis Discussion sections through a comparative genre analysis of theses produced at two public universities in Aceh, Indonesia. Drawing on a qualitative genre-based discourse analysis, the study examines 14 undergraduate theses—seven from each institution—using a move–step framework adapted from Yang and Allison (2003), with frequency criteria proposed by Kanoksilapatham (2005). The analysis focuses on the realization, distribution, and sequencing of rhetorical moves in the Discussion sections. The findings reveal that none of the Discussion sections fully realized the complete move structure proposed in the framework. Instead, undergraduate writers relied on partial and selective use of genre conventions. Reporting results emerged as the only obligatory move across both universities, while commenting on results—particularly through comparison with previous studies—was frequently employed. In contrast, higher-order rhetorical moves related to evaluation, synthesis, and deduction were underrepresented. Although both institutions shared similar overall patterns, notable differences were observed in the extent to which writers engaged in interpretive and evaluative strategies. The study contributes to genre-based ESP research by extending Discussion section analysis to an underexplored undergraduate EFL corpus and by highlighting the influence of institutional context on genre construction. Pedagogically, the findings underscore the need for explicit genre-based instruction to support undergraduate students in developing rhetorically effective Discussion sections.